BioGlue® is not associated with polypropylene suture breakage after aortic surgery - Pacini, Davide; Murana, Giacomo; Hollinworth, David; Northrup, William F.; Arnold, Stacy G.; Di Bartolomeo, Roberto (Frontiers in Surgery, 2022)
Objective We have encountered broken or damaged polypropylene sutures (Prolene®) at the anastomotic sites during aortic reoperations. Because a surgical sealant, bovine serum albumin-glutaraldehyde (BioGlue®), was used in previous aortic surgery in some of these cases, we undertook this in vitro study to evaluate whether the use of BioGlue® was associated with breakage of polypropylene sutures at the aortic anastomosis. Materials and methods The broken polypropylene sutures, anastomotic sites and aortic tissue at the location of suture breakage were visually inspected and evaluated intraoperatively. Six human cadaveric aortic samples were incised circumferentially and anastomosed proximally to a valved conduit with running 4–0 polypropylene sutures (Prolene®). In the test group (n = 3), BioGlue® was applied directly to the Prolene® sutures at the anastomotic sites, while in the control group (n = 3) the anastomoses were not sealed with any surgical adhesive. The six samples were immersed in Dulbecco's phosphate buffered saline solution and mounted on a M-6 Six Position Heart Valve Durability Testing System and tested up to 120 million cycles for a 2-year period. During and upon completion of the testing, the integrity of Prolene® sutures, the anastomosis and aortic tissues was regularly assessed by visual inspection. Results Intraoperative findings included a stretched and thin aortic wall (some with thrombus), a small cleft between the aortic tissue and the Dacron vascular graft. An excessive amount of BioGlue® was often found around the anastomosis, with cracking material, but no signs of mechanical damage were observed in these cases. Upon visual inspection during and after in vitro testing, there was no apparent damage to the polypropylene sutures on the interior or exterior of the aortic anastomoses in any of the samples. No difference was observed in the physical integrity of the polypropylene sutures at anastomotic lines, the anastomoses and aortic tissues between the test and control samples. Conclusions The results of this study suggest that the use of BioGlue® was not associated with breakage of the polypropylene sutures at the anastomotic sites after aortic dissection repair.